Henry Smith Kelley, Laws Applicable to and Governing the City of Saint Joseph, Missouri 192 (1888) - (:unkn) unknown (My University, 1888)
§ 3: No person shall carry on or take part in carrying on, any pistol gallery or shooting gallery, without a license therefor from said city; and the charge for such license shall be five dollars per month.
Keywords: SHOOTING RANGES OR GALLERIES